Factors of preserving and strengthening student's health by pedagodical techologies. - Oleksenko M.V (Kharkov National Pedagogical University, 2011)
Factors of preserving and developing students' health during studies by pedagogical technologies are researched in the article. The ways of eliminating eight basic factors of risk for the youth's health are revealed. It is proved that the usage of the studactive and personally oriented technologies at studies favour upbringing of a healthy person of full value. The dominant role of studactive classes in this process is established. It is defined that on students' health have influence such reasons as surplus nerve emotional tensity, everyday stress, overload, irrational meals, unhealthy ecology.